2013
DOI: 10.1049/el.2012.3633
|View full text |Cite
|
Sign up to set email alerts
|

Compact dual‐wideband bandpass filter using asymmetrical resonator

Abstract: A compact dual-wideband bandpass filter using an asymmetrical resonator is presented. The proposed resonator consists of three uniform microstrip lines of different lengths, and provides not only three transmission poles but also two transmission zeros for each passband. Thus, the bandpass filter has wide bandwidths and sharp cutoff responses. Theory as well as experimential results are given to validate this design concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…Table 2 compares the proposed filter against other stateof-the-art dual-wideband BPFs. It can be observed that filters [1][2][3][4] are all realized using traditional single-layer MMR or resonators in parallel. Almost all of these filters have some common flaws, such as poor band-to-band isolation and limited bandwidth expansion ability of the second passband.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 compares the proposed filter against other stateof-the-art dual-wideband BPFs. It can be observed that filters [1][2][3][4] are all realized using traditional single-layer MMR or resonators in parallel. Almost all of these filters have some common flaws, such as poor band-to-band isolation and limited bandwidth expansion ability of the second passband.…”
Section: Resultsmentioning
confidence: 99%
“…Then dual-wideband can be obtained by providing suitable coupling paths. [1][2][3] Compact high-performance BPFs can be realized using this design method, while the actual applicability is unsatisfactory due to their limited bandwidth expansion capability and poor band-to-band isolation. Another way to realize dualwideband BPFs is to connect several BPFs with lowpass filters of different operation frequencies in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…평행결합선로와 계단형 임피던스 공진 기를 이용한 이중-광대역 대역통과 여파기 [11], [12], 스터브가 연결된 계단형 임피던스 공진기를 이용한 이중-광대역 대역통 과 여파기가 소개되었다 [13]. T형 구조, 평행결합 구조, 비대칭 공진기를 이용한 이중-광대역 대역통과 여파기가 소개되었다 [14]- [16]. …”
unclassified
“…On the other hand, the use of quarter-wavelength stepped-impedance resonators can not only miniaturise circuit size but also widen the stopband by arranging the resonant frequencies in a stagger with the same fundamental frequency. The pin diodes are loaded at the end of the resonators as the switching devices to independently control each passband.Introduction: Bandpass filters (BPFs) are important components for frequency selection because there is a precise prediction of frequency response while the filters are designed [1][2][3][4]. To extend upper stopband bandwidth, stepped-impedance resonators (SIRs) with different dimensions were used to disperse higher-order mode and control transmission zeros [1].…”
mentioning
confidence: 99%
“…Introduction: Bandpass filters (BPFs) are important components for frequency selection because there is a precise prediction of frequency response while the filters are designed [1][2][3][4]. To extend upper stopband bandwidth, stepped-impedance resonators (SIRs) with different dimensions were used to disperse higher-order mode and control transmission zeros [1].…”
mentioning
confidence: 99%